Pengembangan Kampung Budaya Polowijen melalui Ikon Digital Pariwisata Sastra Ragil Kuning sebagai Strategi Bertahan di Masa Pandemi - Rohman, Muhammad Fatoni; zurinani, siti; Fatmawati, Fatmawati (Journal of Innovation and Applied Technology, 2022)
This study offers new perspective in viewing tourism as literature. There was a correlation involving oral literature form as one of tourism attractions. Oral literature-based tourism development was presented in Panji’s story mythology which could be found at Kampung Budaya Polowijen (Polowijen Cultural Village). The icon framing of Ragil Kuning started to be developed and shaped in performing arts and festivals. However, when covid-19 pandemic happened, it significantly effected tourism existence.  In this context, tourism became a sector which was susceptible because of the pandemic. But, on the other hand, tourism sector could also become strong or resilient. The resilience was shown by the strategic efforts done by Kampung Budaya Polowijen’s society to develop digital-based cultural tourism and strengthen the series of Ragil Kuning narraton as the tourism attraction of Kampung Budaya Polowijen.